Modern projects and experiments in organic chemistry : (W. H. Freeman, 2003)
The book consists of: A laboratory manual in two versions: - Miniscale and standard-taper microscale equipment- Miniscale and Williamson microscale equipment; Custom publishing option. All experiments are available though Freeman's custom publishing service at "http: llcustompub.whfreeman.com. Instructors can use this service to create their own customized lab manual, even including they own material; Techniques of the Organic Chemistry Laboratory This concise yet comprehensive companion volume provides students with detailed descriptions of important techniques.